Rapid antigen detection assay for identification of Burkholderia (Pseudomonas) pseudomallei infection. - Anuntagool, A (1996)
A simple antigen detection test was developed for rapid diagnosis of melioidosis caused by Burkholderia (Pseudomonas) pseudomallei infection. The method was based on the use of a specific monoclonal antibody in a sandwich enzyme-linked immunosorbent assay to capture antigen in clinical specimens culture positive for B. pseudomallei. The results showed the sensitivity and specificity of the test to be 75 and 98%, respectively.